Introductory notes on the crisis of the system of “checks and balances” - Gargarella, Roberto (2025)
These lines critically examine the system of checks and balances as the core of modern constitutionalism, designed to prevent mutual oppression between social sectors and promote social peace. Through a historical reconstruction that traces the theory of mixed government, balanced constitutions, and their translation into the separation of powers, it is argued that this institutional framework rested on assumptions that are problematic today: the existence of a few internally homogeneous social groups with stable and irreconcilable interests; the centrality of self-interest as a political motivation; and the possibility of incorporating such interests into constitutional design. On that basis, the system promised representation, mutual controls, and social balance, even at the expense of the majority principle. In the face of the transformations of contemporary societies, characterized by plurality, heterogeneity, and multiculturalism, these assumptions have lost their validity. As a result, the system of checks and balances no longer ensures full representation and effective controls, favoring dynamics of exclusion, concentration of power, and biased normative production.